Effectiveness of Narcotics Addicts, Psychotropic, and Other Addictive Substances in Makassar State Class Detention Houses - -, Syamsir; Renggong, Ruslan; Madiong, Baso (Postgraduate Bosowa University Publishing, 2018)
The purpose of this study was to determine and analyze the effectiveness of the implementation of drug abuse counseling for residents of correctional wards in Makassar Class I Detention Center and to find out and analyze the factors that make ineffective the implementation of drug abuse counseling in Makassar Class I Detention Center. This study uses normative legal research and empirical legal research. Normative research is carried out through literature studies such as law books, readings that are related to the author's research, while empirical research is carried out with field studies through interviews with inmates of the Makassar Class I Detention Center and Makassar Class I Detention Center officers, collecting data at existing research sites. relation to the author's thesis. The implementation of coaching drug abusers in Makassar State Class 1 Detention Houses is less effective due to the failure to achieve the objectives in the development of drug abusers, one of which is forming prison prisoners to become fully human, aware of mistakes, improve themselves, and not repeat the crime so that they can be accepted again. by the community, can actively play a role in development and can live fairly as a good and responsible citizen. It can be seen that the number of drug cases, especially user recidivism, has increased every year, and there are still many drug case recidivism users, from 500 people in Class I remand centers in Makassar to drug users. There are 162 resident users or about 32.4%. 2. The factors that influence the development of drug abusers in Makassar Class I State I detention centers are human resources of Makassar Class I Detention Center correctional officers, inadequate supporting facilities, and awareness of assisted residents in Makassar Class I Detention Center.